Zygomatic arch three-dimensional morphology of capuchin monkeys of the genus Cebus - Da Silva, Jadir D.; Rossi, Ana Cláudia; Watanabe, Luciane N.O.; Ferreira-Pileggi, Beatriz C.; Botacin, Paulo R. [UNESP]; Prado, Felippe B.; Freire, Alexandre Rodrigues (Loki & Dimas, 2024)
The zygomatic arch is an anatomical structure present in humans and monkey species. This study evaluated the three-dimensional morphology of the zygomatic arch of Cebus monkeys through microcomputed tomography scans. 13 dry skulls of Cebus apella from Southeastern Brazil were examined, 6 male and 7 female. The images were segmented in Mimics 18.0 (Materialise, NV, Belgium) software. Measurements were performed in Rhinoceros 5.0 (McNeel & Associates, Seattle, USA). With the transversal measurements, the zygomatic arch was classified as cylindrical (C), elliptical (E) or blade-like (Bl). Statistical analysis was performed by Graph-PAD Prism v.8 software (San Diego, CA, USA) to compare measurements with types and sex. The Two-way ANOVA test with multiple comparisons using the Sidak test was employed to verify the relationship between sexes and types. The significance level was 5%. In males, there was an incidence on the left side of 25% of type E and 25% of type Bl and on the right side of 33% of type E and 17% of type Bl. In females, there was an incidence on the left side of 14% of type E and 36% of type Bl, and on the right side of 14% of type E and 36% of type Bl. The behavior of Cebus apella and its oral habits involving masticatory muscles may be related to the different shapes of the zygomatic arch found, as they have a direct relationship with this cranium structure.
Keywords: Cebus apella; X-ray microtomography; Zygoma